Glucocorticosteroids as dengue therapeutics: resolving clinical observations with a primary human macrophage model. - Sayce, A; Miller, J; Zitzmann, N (Oxford University Press, 2012)
A recent trial [1] investigated the use of a glucocorticosteroid, prednisolone, as a therapy for reduction of severe dengue disease. Many pathogens induce accelerated or excessive inflammation, resulting in detrimental rather than protective effects [2], and dengue virus is a well-characterized example of this phenomenon. Several soluble mediators of the innate inflammatory response have been linked with severe pathology [3]; however, these studies are largely correlative and have failed to elucidate molecular mechanisms facilitating specific pathologies. Nevertheless, continued observation of excessive inflammation concurrent with a drop in viremia and development of severe symptoms [4, 5] has prompted several previous attempts at immunosuppressive strategies as a means of reducing severe dengue disease [6–9]